2005
DOI: 10.1113/jphysiol.2004.081323
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the heart to ischaemia–reperfusion injury and exercise‐induced cardioprotection are sex‐dependent in the rat

Abstract: The cardioprotective effects of short-term exercise against myocardial ischaemia-reperfusion injury in male and female rats were examined. We subjected male and female rats to 0 (Sed; n = 8 males and 8 females), 1 (1 day; n = 10 males and 8 females), or 5 (5 day; n = 6 males and 6 females) days of treadmill running. Langendorff-perfused hearts underwent 1 h of regional ischaemia and 2 h of reperfusion, and infarct size (expressed as a percentage of the zone at risk; ZAR), left ventricular pressure development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
119
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 43 publications
15
119
0
2
Order By: Relevance
“…Early studies in myocytes from exercised hearts revealed that cardiac K ATP channel opening elicited resistance to anoxic stress, while the nonselective K ATP channel inhibitor, glibenclamide, abolished this protection (28). Follow-up study indicated that exercise stimulated overexpression of the sulfonylurea receptor portion of the sarc K ATP channel promoted protection against IR injury (15). Selective pharmacological blockade of the sarc K ATP channel demonstrated an essential role for this channel against long-duration ischemic insults, although protection against IR-generated arrhythmias was not evaluated (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in myocytes from exercised hearts revealed that cardiac K ATP channel opening elicited resistance to anoxic stress, while the nonselective K ATP channel inhibitor, glibenclamide, abolished this protection (28). Follow-up study indicated that exercise stimulated overexpression of the sulfonylurea receptor portion of the sarc K ATP channel promoted protection against IR injury (15). Selective pharmacological blockade of the sarc K ATP channel demonstrated an essential role for this channel against long-duration ischemic insults, although protection against IR-generated arrhythmias was not evaluated (12).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, we undertook the present investigation to test the hypothesis that the mito K ATP channel is essential for exercisemediated protection against IR-generated arrhythmias. Results from previous investigations of exercised hearts indicate the sarc K ATP channel is essential for myocardial infarct sparing effects of exercise (12,15,17). Thus we also tested the rival hypothesis that the sarc K ATP channel was responsible for the anti-arrhythmic protection provided by exercise.…”
mentioning
confidence: 99%
“…[22] Pharmacologic inhibitor experiments further showed that reduced myocardial injury in females was dependent on the phosphatidylinositol-3 kinase and protein kinase C epsilon (PKCε) signaling pathways. Brown et al [23] demonstrated in a similar model that protection from injury in females was dependent on functional sarcolemmal K ATP channels. Wang et al performed in vitro, global ischemia experiments in Langendorff-perfused mouse hearts subjected to 20 minutes of ischemia followed by 60 minutes of reperfusion and observed reduced myocardial injury in female compared to male hearts, an effect that was lost in estrogen receptor α knockout mice supporting a role for this estrogen receptor isoform.…”
Section: Myocardial Injury Modelsmentioning
confidence: 99%
“…28,29 At the end of the two hours of reperfusion, a colloidal pigment -Blue Evans (Evans blue, Sigma E2129) was administered in bolus through the femoral vein, in the amount of 4-5 ml for the delimitation of the infarct risk area. The heart is quickly dissected, the right ventricle is removed and the mentioned areas are excised.…”
Section: Quantification Of the Experimentally Achieved Infarctionmentioning
confidence: 99%